Harry Wild. Series 4 [videorecording (DVD)] - Logan, David, 1969- (Acorn, 2025)
From an international assassination attempt to a literary-inspired murder, Harry and Fergus find themselves improving on the police solve rate as they tackle their most elusive and dangerous cases yet.